Food and nutritional education as a practice at school: The teacher’s view (Research, Society and Development, 2023)
This article came to be in a master's degree research, to which was applied a focus group method to a Porto Alegre private schooling institution's teaching body, having as its overall objective to probe both knowledge and accession towards Nutritio-nal and Dietary Education (NDE) in private schooling environments. To support this study, it was used a theoretical reference mainly based on brazilian legislature and educational authors. The focus group results were analyzed in three axes of discus-sion: axis 1: the adult's reference as a frame to one's formation; axis 2: the importance of the teacher's graduation to establish NDE in a schooling environment; axis 3: the importance of NDE in a schooling environment. From the accomplished analysis, it is displayed the importance of an adequate preparation for education professionals and the enactment of NDE in an orga-nized manner in a school program with strategies that include said attainments as part of a schooling culture aiming to address schooling community as a whole.